Growth and characterization of AlxGa1−xN lateral polarity structures. Issue 5 (18th November 2014) - Hoffmann, Marc Patrick; Kirste, Ronny; Mita, Seiji; Guo, Wei; Tweedie, James; Bobea, Milena; Bryan, Isaac; Bryan, Zachary; Gerhold, Michael; Collazo, Ramon; Sitar, Zlatko
Abstract AlGaN lateral polarity structures (LPS) with varying Al composition, have been fabricated by metalorganic chemical vapour deposition on LPS templates containing µm size domains. III‐metal and N‐polar AlGaN domains have been grown on LT‐AlN and c‐sapphire domains, respectively. LPS characterization by SEM and AFM reveals two major effects when the Al composition has been varied: (a) A high Al content leads to columnar growth within N‐polar domains and (b) a height difference between the polar domains can be observed for low Al compositions towards III‐polarity. The surface quality of the III‐polar domains is not effected by the Al composition. The surface roughness of N‐polar domains decreases for lower Al compositions. The high periodicity of the polar domains and the high quality of the boundary between domains suggest a high potential of AlGaN LPS to be used as lateral wave guides for quasi phase matching.